Aerosol-Assisted Chemical Vapor Deposition of Silver Thin Film Electrodes for Electrochemical Detection of 2-Nitrophenol. Issue 7 (17th May 2018) - Ehsan, Muhammad Ali; Aziz, Md. Abdul; Rehman, Abdul; Hakeem, Abbas Saeed; Qasem, Mohammed Ameen Ahmed; Ahmad, Syed Haseeb Ali
Abstract : Present work reports a simple, cost-effective and facile approach for electrochemical sensing of 2-nitrophenol (2-NP) as the model analyte using silver thin film electrodes. Thickness controlled silver thin films are grown on ITO glass substrates at 400°C for varying deposition times of 10–45 minutes using methanol solution of silver triflouroacetate (Ag(CF3 COO)), via aerosol assisted chemical vapor deposition (AACVD). XRD, XPS, SEM and EDX analysis of the films verified the presence of crystalline and phase pure elemental silver with micro/nanometer dimensions whereas a growth pattern from spherical nanoparticles to continuous thin films is observed over time. All Ag-electrodes were used to investigate the electrochemical behavior of 2-NP by cyclic voltammetry (CV) while the quantitative profiling was done by LSV. The results indicate that the Ag-electrode developed in 30 min manifested excellent electrocatalytic activity toward 2-NP reduction, thereby lowering the reduction overpotential and increasing the reduction current which is attributed to the percolated metallic network in its micro/nanostructure. This particular electrode exhibited a dynamic range = 50–450 μM, detection limit = 12 nM, and high selectivity from potential interfering agents, a performance much better than the available thin film sensors and Ag-disk electrode.